Dry fermenters for biogas production - Yousuf, Abu; Karim, Ahasanul; Islam, Mohammad Amirul; Karim, Shefa Ul; Khan, Maksudur R.; Che Ku Mohammad Faizal, Che Ku Yahya (Elsevier Inc., 2020)
The depletion of nonrenewable energy sources drives the exploration for renewable energy sources as an alternation route of energy generation. Hence, in the past decade, research efforts have been employed to explore potential renewable energy sources utilizing waste biomass. Anaerobic digestion (AD) is considered as an efficient technique to treat different kinds of wastes such as agricultural, industrial, and food wastes to produce renewable energy. Until now, two predominant fermentation processes, namely submerge or liquid-state anaerobic fermentation (LSAF) and dry or solid-state anaerobic fermentation (SSAF) have been implemented to extract energy from waste biomass. Nowadays, SSAF is claimed to be more advantageous than LSAF for a number of reasons including its comparatively smaller reactor volume, lower energy requirements for heating, minimal material handling, and lower total parasitic energy loss. Due to its low moisture content, the digestate of SSAF can be used as fertilizer or pelletized fuel, which is much easier to handle than the effluent from LSAF. However, for enhancing the performance of dry AD processes, a suitable reactor needs to be designed so that the maximum amount of substrate could be fermented, to make the technology more economically viable. Therefore this chapter is aimed at discussing the different kinds of bioreactors along with their potential benefits, challenges, and limitations, which have been explored recently for biogas production through dry fermentation.